Sexo, poder y espiritualidad en un monasterio femenino colonial. Las monjas de la Encarnación, Popayán, siglo XVII - Abadía Quintero, Carolina; Rodríguez Jiménez, Pablo (Jahrbuch für Geschichte Lateinamerikas, 2025)
Few events could cause a greater scandal in colonial society than rumors about the sinful conduct of cloistered nuns. Because, contrary to what one might think, there were nuns who, in multiple ways and in various cloisters in the Indies, led acts of indiscipline, disobeyed bishops and judges, and had illicit relationships in defiance of male authority and professed religious vows. This is the case of the Augustinian nuns of the convent of Nuestra Señora de la Encarnación in Popayán, who were accused of various acts of sacrilege against themselves and against the cloister, causing an evident tension between estates, an assassination attempt on the person of the bishop, and the execution on the gallows of a foreigner. The interrogations and trials that make up the process show how the rumors about what was happening in the convent exalted the spirits of the relatives of the nuns, authorities and neighbors, who between 1608 and 1613, got involved in a strong dispute to condemn or defend the Augustinians, and whose outcome was to be exiled to convents in Pasto and Quito. Among the objectives of this text is to analyze a prohibited sexuality, as well as the rumors and testimonies of carnal relations that supported the accusations against the nuns, and that ultimately generated the challenge from neighbors and civil authorities to the episcopal figure and the scandal that the city experienced.